A framework for financial analysis - Ford, John Kingston (Englewood Cliffs, N.J. : Prentice-Hall, 1981)
The book provides an introduction to the concepts and techniques of financial analysis.
Includes bibliographical references and index.
hza 10/09/2018
Loans
Keywords: Financial statements; Business enterprises